Translator Training: Teaching Translation and Interpreting in the 21st Century (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
In the 21st century, a lot more is expected of professional translators and interpreters than solely linguistic fluency. Employers now tend to seek professionals who can adapt and thrive in today’s evolving economy. This entails they need to be highly skilled, adaptable, willing to embrace technology and incorporate it into their work, while continually advancing their professional development. They must also demonstrate strong communication skills, creativity, teamwork, as well as be ready to tackle ongoing intellectual challenges. This necessitates a revision of current translation and interpreting educational programmes to meet the industry’s evolving needs and the challenges posed by AI technologies. The aim of this paper is to, first of all, examine the roles of translators and interpreters nowadays, as well as to have a closer look at the forecasts concerning the future of the translation profession, with a view to specifying the relevant competencies that need to be trained to help students successfully enter and then thrive in the translation industry. The paper also outlines certain aspects that need to be taken into consideration when designing translator an interpreter training programmes at both the undergraduate and postgraduate level. Among other things, this research draws the reader’s attention to the fact that, in the 21st century, translation and interpreting courses must not only cover the latest AI advancements and their potential to enhance work effectiveness, but also address several key areas related to legal and ethical issues, soft skills, as well as technological limitations. It is the author’s hope that, when adapted to these considerations, translation and interpreting training programmes will better prepare students to succeed in the fast-evolving industry, while upholding high standards of linguistic and cultural accuracy.